THE INFLUENCE OF WORK FROM HOME, JOB STRESS, AND WORKLOAD ON THE PERFORMANCE OF HIGH SCHOOL TEACHERS AT SMA N 32 JAKARTA - Achmad Sauqy; Muhammad Mifdhal; Siti Fatimah Dara Airangga (Green Publisher, 2023)
Teacher performance during the Covid 19 pandemic is essential for effective and efficient learning. This study aimed to analyze the Effect of Work From Home (WFH), Work Stress, and Workload on Teacher Performance at SMA N 32 Jakarta. This study uses an associative approach. In this study, there were 55 teachers at SMA N 32 Jakarta—data collection technique using a questionnaire. The sampling technique used in this study was saturated sampling, so the number of samples obtained was 55 respondents. Data analysis used the F test, t-test for hypothesis testing, and multiple linear regression analysis. The results showed that based on simultaneous testing, it was found that work from home, workload, and competence simultaneously or simultaneously had a significant effect on teacher performance at SMA N 32 Jakarta. Based on partial testing, working from home positively and significantly affects teacher performance at SMA N 32 Jakarta. Based on partial testing, work stress does not affect teacher performance at SMA N 32 Jakarta. Based on partial testing, the workload does not affect teacher performance at SMA N 32 Jakarta. So that educational institutions should pay more attention to the variables of work from home, work stress, and workload because they significantly improve teacher performance